Stability of Aspiration Status in Healthy Adults. (May 2013) - Todd, J. Tee; Stuart, Andrew; Lintzenich, Catherine R.; Wallin, Jordan; Grace-Martin, Karen; Butler, Susan G.
Objectives: In multiple separate studies, we consistently found that approximately 30% of asymptomatic healthy older adults silently aspirated liquids during flexible endoscopic evaluation of swallowing (FEES). We subsequently questioned whether aspiration status remained stable in healthy older adults over time. The purpose of this study was to determine the stability of aspiration status in healthy older adults over time. Methods: Eighteen healthy older participants, comprising of 9 aspirators and 9 nonaspirators whose aspiration status was identified in a previous study, underwent a second FEES approximately 6 to 21 months later. The participants contributed 36 swallows, comprising 5-, 10-, 15-, and 20-mL boluses of milk (ie, 1 bolus of each volume of skim, 2%, whole, and soy milk) and water via cup and straw delivery, during the original FEES. An abbreviated protocol was administered for the repeat FEES. The Penetration-Aspiration Scale was used to rate all swallows. Results: A McNemar test demonstrated no change in aspiration status among participants between the initial test and the retest (p > 0.999). Conclusions: In this cohort, the aspiration status was stable over about 12 months. This finding lends credence to the premise that trace aspiration of liquids may be a normal and consistent finding in some healthy older adults.